Victorian and Edwardian Virtual Reality: from Stoker to Forster - Catherine Lanone (Cahiers Victoriens et Edouardiens)
Fantasies of global transmission haunted the Victorian era, as demonstrated by one of George Du Maurier’s cartoons. Dracula engages with transmission in a dual way, turning Mina’s mind into a radio-system which the Count may switch on and off, whereas Van Helsing may reverse the signal and spy on the vampire; technology embodying modernity, from the phonograph to the typewriter or telegraph, may vanquish the Count’s archaic powers of transmission. E. M. Forster’s 1909 short story ‘The Machine Stops’ evidences on the contrary a dystopian distrust of technology. With acute intuition, Forster envisions a network of long distance communications, and challenges the potential human dependence on prosthetic technology. He advocates instead a return to true human contact.